Dilema Program Adiwiyata: Antara Idealitas dan Realitas Implementasi di Kepulauan Riau - Muhammad Yunus; Mulia Wiwin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This article examines the implementation dilemma of the Adiwiyata Program in Riau Islands Province, focusing on the gap between policy ideals and actual practice. Employing a qualitative approach with the CIPP evaluation model (Context, Input, Process, Product), the study evaluates policy, planning, implementation, and outcomes of the program. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that while the policy framework complies with standards, the planning, implementation, and outcomes are yet to be optimized. Major issues include inconsistency in execution, weak stakeholder coordination, and ineffective assessment of Adiwiyata schools. This study contributes theoretically to the evaluation of environmental education policy and offers strategic recommendations for strengthening program governance at the provincial level. The novelty of this research lies in its focus on provincial-level evaluation, contrasting with previous studies centered on schools. The findings are expected to inform the development of more effective and sustainable environmental education policies.